The social origins of Islam : mind, economy, discourse - Bamyeh, Mohammed A. (University of Minnesota Press, 1999)
The story of the origins of Islam provides a rich and suggestive example of sweeping cultural transformation. Incorporating both innovation and continuity, Islam built upon the existing cultural patterns among the peoples of the Arabian peninsula even as it threatened to eradicate these same patterns. In this provocative interdisciplinary study, Mohammed A. Bamyehcombines perspectives from sociology, literary studies, anthropology, and economic history to examine the cultural ecology that fostered Islam.